2015
DOI: 10.1245/s10434-015-5012-3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool for Predicting Major Complications After Cytoreductive Surgery with Hyperthermic Intraperitoneal Chemotherapy

Abstract: Background Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) has an emerging role in the treatment of peritoneal malignancies. The CRS-HIPEC approach has known treatment-related toxicities. This study sought to determine the predictors of major postoperative complications after CRS-HIPEC in a high-volume center. Methods From a single-institution database, this study investigated complications experienced by patients undergoing CRS-HIPEC. Multiple preoperative and operative fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 32 publications
1
15
2
Order By: Relevance
“…The median intensive care unit (ICU) stay and overall hospital stay were 3 and 16 (10.5‐26.5), respectively. The median highest postoperative platelet count was 423 (284‐743) × 10 9 /l; and was encountered at a median of 10 days following surgery. Overall, 90 (46.9%) patients developed postoperative thrombocytosis (>450 × 10 9 /l); of them, 25 (13.0%) experienced extreme thrombocytosis (>1000 × 10 9 /l).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median intensive care unit (ICU) stay and overall hospital stay were 3 and 16 (10.5‐26.5), respectively. The median highest postoperative platelet count was 423 (284‐743) × 10 9 /l; and was encountered at a median of 10 days following surgery. Overall, 90 (46.9%) patients developed postoperative thrombocytosis (>450 × 10 9 /l); of them, 25 (13.0%) experienced extreme thrombocytosis (>1000 × 10 9 /l).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies that investigated mortality rates in patients who underwent CRS/HIPEC reported an incidence of 3-10% of all VTE events. 4,9,15 However, most of those studies identified only DVT and PE as VTE, with the occurrence of PSMVT assessed in only a few of them. 8,9 Interestingly, in our cohort, PSMVT was the most common thrombotic complication.…”
Section: Follow-up Datamentioning
confidence: 99%
“…Intraperitoneal (IP) chemotherapy is used to achieve an increased concentration of the anticancer drugs in the peritoneal cavity and to reduce systemic exposure [5]. IP therapy using mildly heated drug solutions, Hyperthermic IntraPeritoneal Chemotherapy (HIPEC), further enhances drug penetration into malignant tissue, and combining HIPEC with cytoreductive surgery results in improved efficacy of the treatment [69]. Encapsulation of cytotoxic drugs in nanoformulations has been also shown to improve the anticancer effect of IP chemotherapy [10].…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to identify any factors associated with major morbidity or mortality, presumably because of the small number of patients, but did observe a higher ICU length of stay in those with a major complication. Recently, a novel tool to predict major morbidity and identify low-risk patients who are likely to benefit from CRS/HIPEC has been described and may be useful during preoperative counseling of patients with PC (28). As a new CRS/HIPEC center, we have also been fortunate to collaborate with St Jude Children's Research Hospital in the management of pediatric and young adult patients with desmoplastic small round cell tumor (DSRCT).…”
Section: Discussionmentioning
confidence: 99%